Development of guava (Psidium guaiava Linn.) powder - Rasco, Elisa T.; De Leon, Sonia Y.
Experiments were conducted to determine the quality of a guava powder produced by soaking in salt solution, sulfiting, increasing the soluble content and drying in vacuum oven at a temperature of 150°F and 27" pressure. There were three phase in the study. Phase I was on the determination of the best soaking time an concentration of salt solution. In this phase, the concentrations (0 and 2%) salt solution and soaking times of 10, 20 and 30 minutes were studied. The results revealed that soaking in 2% salt solution for 10 minutes gives a guava powder of improved appearance and flavor. The product was light brown to light yellow, with a characteristics guava odor and flavor. It was rated 'like moderately" by the panel of judges. Phase II was on the determination of the best concentration of sodium bisulfite solution and time of dipping. Three sodium bisulfite concentrations (0.1%, 0.2% and 0.3%) and length of dipping (10, 20 and 30 minutes) were studied. Results of the study showed that the longer guavas are dipped in the sulfite solution and the more SO2 retained by the guava, the better is the color of the guava powder. No significant difference was found between the samples with regards to flavor and acceptability. However, the sample dipped in 0.3% NaHSO3 for 10 minutes was chosen since it received higher mean scores than the other samples. It was light yellow in color, slight to characteristic guava odor and flavor and was rated "like slightly" to "like moderately". The last phase of the study was on the determination of the effect of increasing the percentage soluble solids on the quality of the guava powder. Results of the objective tests showed that increasing soluble solids content by dipping the guava in a prepared sirup increased the yield of the resulting powder. It brought about a decrease in the moisture content of the final product. The SO2 retention was also reduced. Subjective tests favored the increase in soluble solids content to color which was described as light to yellow to white. However, with regards to odor, flavor and acceptability, it resulted in less intensity of guava odor and flavor and lower acceptability rating. It had slight guava odor and flavor and was rated "like slightly" by the judges.
Appendices: leaves 45-72.
Chiefly tables.
Thesis (A.B.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Guava -- Preservation